Genetic diversity and population structure of the blue jack mackerel Trachurus picturatus across its western distribution. Issue 5 (8th April 2019) - Moreira, Cláudia; Correia, Alberto T.; Vaz‐Pires, Paulo; Froufe, Elsa
Abstract : Blue jack mackerel Trachurus picturatus collected at six sampling locations of the north‐east Atlantic Ocean (Azores, Madeira, Canaries, and Matosinhos, Peniche and Portimão, mainland Portugal) and one location in the Mediterranean (Sicily), were used to examine the genetic structure of this species. Three mitochondrial gene regions (cytochrome c oxidase subunit I, cytochrome b and control region) were used to study the genetic structure of the species in Macaronesia, as well as to compare the genetic diversity of this region with published results from its eastern distribution. All markers indicated the absence of genetic structure among populations, with high indices of genetic diversity. These results suggest that the species went through a bottleneck event, followed by a recent population expansion. Moreover, the comparison with previously published results from the T. picturatus Mediterranean distribution suggests the existence of a single panmictic population throughout the species' full range. This was, however, an unexpected result since other methodologies have shown the presence of, at least, three different population‐units in the NE Atlantic Ocean.